Retrospective analysis of serology and radiology results in patients with suspected cystic echinococcosis through 3 years period - KARAHASAN, AYŞEGÜL (My University, 2023)
Objective: Cystic echinococcosis (CE), caused by the larval stage of Echinococcus granulosus sensu latu, is one of the neglected zoonotic infectious diseases and Türkiye is among the endemic countries. This study was designed to analyze serology results for patients who were diagnosed as CE by clinical symptoms and radiological methods over a three-year period. Methods: Sera were analyzed for Anti-E. granulosus IgG by a chemiluminescence immunoassay (CLIA) (HYDATIDOSIS VIRCLIA® IgG MONOTEST, Vircell) using the VIRCLIA® (CLIA; Vircell, Granada, Spain) and results processed by the dedicated software. Cutoff for a positive test was ≥1.1 index value. Echinococcal cysts were detected based on ultrasonography, computed tomography, and magnetic resonance imaging. Results: A total of 244 sera were analyzed from 109 patients, during three-year-period from January 2018 to December 2020. Anti-E. granulosus IgG was ordered twice in 89 patients, three times in 15 patients, four times in four patients, and five times in one patient. CLIA test was positive among 41 of 109 (37.6%) patients in whom 32 (76%) had only hepatic involvement, whereas in 5 (12%) hepatic and pulmonary involvement were coexisted. The mean age of seropositive patients was 39.8 (6-75±2.72) and 61.9% of them (n=26) were female. Time intervals between sequential test orders varied from 1 day to 33 months. Eight seropositive patients turned out to be negative, and one of 66 seronegative patients became seropositive. Positive test results were converted to negative in the case of therapy or cyst inactivit

Amaç: Echinococcus granulosus sensu latu’nun larval evresinin neden olduğu kistik ekinokokkoz (CE), ihmal edilen zoonotik enfeksiyon hastalıklarından biridir. Türkiye CE açısından endemik ülkeler arasında yer almaktadır. Bu çalışma, klinik semptomlar ve radyolojik yöntemlerle CE tanısı konan hastaların seroloji sonuçlarını üç yıllık bir süre içinde analiz etmek için tasarlanmıştır. Yöntemler: Serum örnekleri VIRCLIA® (CLIA; Vircell, Granada, İspanya) kullanılarak bir kemilüminesans immünoanaliz (CLIA) (HYDATIDOSIS VIRCLIA® IgG MONOTEST, Vircell) yöntemi ile anti-E. granulosus IgG için analiz edildi ve sonuçlar özel bir yazılım programı kullanılarak değerlendirildi. Pozitif sonuç için indeks değeri ≥1,1 olarak belirlendi. Ekinokok kistlerinin tespitinde ultrasonografi, bilgisayarlı tomografi ve manyetik rezonans görüntüleme kullanıldı. Bulgular: Ocak 2018-Aralık 2020 tarihleri arasında 109 hastadan toplam 244 serum analiz edildi. Anti-E. granulosus IgG 89 hastada iki kez, 15 hastada üç kez, dört hastada dört kez ve bir hastada beş kez istendi. CLIA testi hastaların 41’inde (37,6) pozitif bulundu ve bu hastaların 32’sinde (%76) sadece karaciğer turulumu var iken, 5’inde (%12) akciğer ve karaciğer tutulumu birlikte saptandı. Seropozitif hastların yaş ortalaması 39,8 (6-75±2,72) olup, %61,4’ü kadındı. Ardışık test istemleri arasındaki zaman aralıkları 1 gün ile 33 ay arasında değişiyordu. İzlem sürecinde 8 seropozitif hasta negatife dönerken 66 seronegatif hastadan biri seropozitif oldu. Pozitif serolojinin tedavi veya kist inaktivasyonu durumunda negatife dönüştüğü belirlendi. Sonuç: CLIA’nın CE hasta takibi için tamamlayıcı bir tanı yöntemi olarak kullanılabileceği sonucuna varabiliriz.
Kistik ekinokkoz şüphesiyle serolojik ve radyolojik değerlendirme yapılan hastaların üç yıllık periyotta retrospektif analizi
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Cystic echinococcosis; CLIA; serology; radiology; Kistik ekinokokkoz; seroloji; radyoloji